Analysis of the potential of ethanol extract from small star fruit (Averrhoa bilimbi L) as a smear layer remover: Analisis potensi ekstrak etanol buah belimbing wuluh (Averrhoa bilimbi L) sebagai pembersih smear layer - Nur Asmah; Indrya Kirana Mattulada; Syamsiah Syam; Ika Shabrina; Nurul Fauzia Amanda (Makassar Dental Journal PDGI Makassar, 2026)
Root canal treatment aims to remove vital and non-vital pulp tissue from the root canal. The smear layer consists of residual of RCT containing organic and inorganic matter from the root canal. Ethylenediaminetetraacetic acid (EDTA 17%) is used as an irrigant to remove the smear layer, but it is toxic to periapi-cal tissues. One natural irrigant that is safe for periapical tissues is the extract of star fruit (Averrhoa bilimbi L.), which contains active compounds such as sapo-nins, flavonoids, and tannins that have potential to remove smear layer. This article reports on the potential of BBW ethanol extract as a smear layer cleaner. This laboratory experimental study, employing a post-test only control design, involved 24 single-rooted teeth divided into 4 treatment groups with 6 replicates. Assessment was performed using confocal laser scanning microscopy based on the Hulsmann scoring system, followed by statistical analysis. Based on the Mann-Whitney test, the comparison between the treatment groups (17% EDTA) and the 35% extract showed a p-value of 0.269, indicating no significant dif-ference. It was concluded that the 35% ethanol extract of belimbing wuluh fruit is effective in removing the smear layer and has potential as a natural root ca-nal irrigation agent.